Genetic Assembly of Double-Layered Fluorescent Protein Nanoparticles for Cancer Targeting and Imaging - Kim, Seong-Eun; Jo, Sung Duk; Kwon, Koo Chul; Won, You-Yeon; Lee, Jeewon (WILEY, 2017)
Hepatitis B virus capsid (HBVC), a self-assembled protein nanoparticle comprised of 180 or 240 subunit proteins, is used as a cage for genetic encapsulation of fluorescent proteins (FPs). The self-quenching of FPs is controlled by varying the spacing between FPs within the capsid structure. Double-layered FP nanoparticle possessing cancer cell-targeting capabilities is also produced by additionally attaching FPs and cancer cell receptor-binding peptides (affibodies) to the outer surface of the capsid. The generically modified HBVC with double layers of mCardinal FPs and affibodies (mC-DL-HBVC) exhibit a high fluorescence intensity and a strong photostability, and is efficiently internalized by cancer cells and significantly stable against intracellular degradation. The mC-DL-HBVC effectively detects tumor in live mice with enhanced tumor targeting and imaging efficiency with far less accumulation in the liver, compared to a conventional fluorescent dye, Cy5.5. This suggests the great potential of mC-DL-HBVC as a promising contrast agent for in vivo tumor fluorescence imaging.